PERAN MAHASISWA KKN UNIVERSITAS NEGERI PADANG DALAM MENINGKATKAN PENDIDIKAN KUALITAS BELAJAR SISWA SD NEGERI 10 PADANG SAGO MELALUI PROGRAM PRIVATE CLASS - Aslimeri; Annisa Alya Firstira; Beri Khasih Ardian; Hanna Fadilah; Novità Rahmadhani; Nurul Prima Wilva (Jurnal IKEOR, 2025)
The Community Service Program (KKN) at Padang State University (UNP) plays a crucial role in improving education within the community. This article examines the contribution of UNP KKN students in supporting the learning process of students at SDN 10 Padang Sago through the Privat Class program. This program is a form of intensive, individualized supplementary tutoring aimed at facilitating students’ understanding of difficult material, enhancing their enthusiasm for learning, and fostering their self-confidence in participating in lessons. The program utilizes participatory methods through observation, interviews, and documentation. Results demonstrate improved mastery of the material, a higher enthusiasm for learning, and active student participation in the learning process. In addition to its positive impact on students, the program also strengthens the communication skills and social empathy of the KKN students. Thus, Privat Class serves as concrete evidence that student involvement can positively contribute to improving the quality of basic education in schools.